The reverse Warburg Effect: Glycolysis inhibitors prevent the tumor promoting effects of caveolin-1 deficient cancer associated fibroblasts - Bonuccelli, Gloria; Whitaker-Menezes, Diana; Castello-Cros, Remedios; Pavlides, Stephanos; Pestell, Richard G.; Fatatis, Alessandro; Witkiewicz, Agnieszka K.; Vander Heiden, Matthew G.; Migneco, Gemma; Chiavarina, Barbara; Frank, Philippe G.; Capozza, Franco; et al. (Cell cycle (Georgetown, Tex.), 2010)
We and others have previously identified a loss of stromal caveolin-1 (Cav-1) in cancer-associated fibroblasts (CAFs) as a powerful single independent predictor of breast cancer patient tumor recurrence, metastasis, tamoxifen-resistance, and poor clinical outcome. However, it remains unknown how loss of stromal Cav-1 mediates these effects clinically. To mechanistically address this issue, we have now generated a novel human tumor xenograft model. In this two-component system, nude mice are co-injected with i) human breast cancer cells (MDA-MB-231), and ii) stromal fibroblasts (wild-type (WT) versus Cav-1 (-/-) deficient). This allowed us to directly evaluate the effects of a Cav-1 deficiency solely in the tumor stromal compartment. Here, we show that Cav-1-deficient stromal fibroblasts are sufficient to promote both tumor growth and angiogenesis, and to recruit Cav-1 (+) micro-vascular cells. Proteomic analysis of Cav-1-deficient stromal fibroblasts indicates that these cells upregulate the expression of glycolytic enzymes, a hallmark of aerobic glycolysis (the Warburg effect). Thus, Cav-1-deficient stromal fibroblasts may contribute towards tumor growth and angiogenesis, by providing energy-rich metabolites in a paracrine fashion. We have previously termed this new idea the "Reverse Warburg Effect". In direct support of this notion, treatment of this xenograft model with glycolysis inhibitors functionally blocks the positive effects of Cav-1-deficient stromal fibroblasts on breast cancer tumor growth. Thus, pharmacologically-induced metabolic restriction (via treatment with glycolysis inhibitors) may be a promising new therapeutic strategy for breast cancer patients that lack stromal Cav-1 expression. We also identify the stromal expression of PKM2 and LDH-B as new candidate biomarkers for the "Reverse Warburg Effect" or "Stromal-Epithelial Metabolic Coupling" in human breast cancers.